Analysis of UIN Jakarta Students' Perception Towards Syariah Savings at BSI Bank - Raza Syarif Hidayatullah; Windy Rizki Amelia; Nurul Sondang Diniari; Abdullah Azzam (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the perceptions of students of the State Islamic University of Jakarta towards sharia savings at Bank Syariah Indonesia (BSI). As a young generation who are technologically and financially literate, students are an important segment in the growth of Sharia banking. This study uses a quantitative method with a survey approach, involving 30 randomly selected respondents. Data were collected through a questionnaire that measured satisfaction, trust in sharia principles, product excellence, ease of service access, and interest and loyalty. Descriptive statistical analysis and one-sample t-test were used to assess students' overall perceptions. The results show that students' perceptions of Sharia savings at Bank BSI are generally positive. Respondents are satisfied with BSI's services, believe in sharia principles, and assess the product according to their needs. However, it is necessary to improve service accessibility and education related to product features to strengthen financial inclusion.